THE EFFECTIVENESS OF COMMUNITY LANGUAGE LEARNING METHOD TOWARD STUDENTS SPEAKING ABILITY AN EXPERIMENTAL RESEARCH FOR EIGHT GRADE OF SMPN 3 BANJARBARU - Fizi, Ridhani (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2024)
Abstract English speaking ability an experimental is one of the language skill which become the main purpose for the English language learner at the school. The purpose of CLLM is to help the students to communicate in their daily life, but the achievement of the CLLM is felt difficult practically, because in fact, many students are still passive in the classroom. When the students communicate in the target language, students might encounter a situation in which they cannot find words to convey meaning. When the flow of communication in this situation of communication breakdown, they used Community Language Learning Method (CLLM) method to prevent the stagnation in conveying that messages and make the students find it enjoyable to learn. Therefore, this study concerns with students’ ability in learning English by using CLLM.This study is attempt to discover students’ speaking ability for the eight year students’ of SMPN 3 Banjarbaru in the school year 2023/2024. Two research questions formulated: (1) to what extent is the achievement of the speaking ability for the eight year students of SMPN 3 Banjarbaru in the school year 2023/2024? (2) to what extent is the effect of CLL toward students’ speaking ability for the eight year students of SMPN 3 Banjarbaru in the school year 2023/2024?This study was experimental research. So there were two groups of sample, they were experimental and control groups. The population of this study was 160 students. The researcher took 40 students as the sample. As the research instruments which was developed to collect data, the researcher provided some pictures, the students were asked to describe the pictures. While the students were describing the pictures, the researcher recorded it.After collecting and calculating the data, the researcher found that the mean score of pre-test and post-test for experiment group were 46.45 and 51.85, while for control group were 41.2 and 45.3. And in testing the hypothesis, the researcher used t-test formula. The researcher found that t-test was 2.280 and t-table in significant rank 0.05 (5%) was 2.021. It proved that t-test was higher than t-table (2.280 > 2.021). So the alternative hypothesis was accepted. It indicates that Community Language Learning Method (CLLM) was effective in speaking teaching for the eight year students of SMPN 3 Banjarbaru in the school year 2023/2024.